Putusan Sengketa Laut China Selatan Serta Implikasi Hukumnya Terhadap Negara Disekitar Kawasan Tersebut - Darajati, Muhammad Rafi; Adolf, Huala; -, Idris (UI Scholars Hub, 2018)
One of interesting developments about the global security is the issue of territorial disputes in the South China Sea between Philippines and China. Philippines has brought the dispute to the Permanent Court of Arbitration. The ruling from Permanent Court of Arbitration said that China’s claim about a nine-dash line does not have a legal basis. However, China rejects the ruling and remains aggressive which might cause instability in South China Sea region. This research aims to look at the implications of the ruling of the Permanent Court of Arbitration for State Parties and states around the South China Sea region. Authors use juridical normative research method with literature studies. This research shows that States Parties have to implement and respect the ruling because it has already become the source of international law. For the states that located around the region, the ruling also has an effect to facing China’s aggressiveness and rules handling maritime claims in the South China Sea region.